Proof of Work as a Three-Sided Market - Berg, Chris; Davidson, Sinclair; Potts, Jason (Frontiers in Blockchain, 2020)
Blockchain technology is the distributed, decentralised ledger technology underlying Bitcoin and other cryptocurrencies. We apply Oliver Williamson’s transactions cost analysis to the blockchain consensus mechanism. Blockchains reduce the costs of opportunism but are not ‘trustless’. We show that blockchains are trust machines. Blockchains are platforms for three-sided bargaining that convert energy-intensive computation into economically-valuable trust.